The Effect of Variations in Impeller Shape on Discharge and Water Pressure on the Pump Prototype - Fajar Riyanto; Arasy Fahruddin; Edmundo Tiago Belo (Universitas Muhammadiyah Sidoarjo, 2022)
A pump is a device used to move fluid or something in the form of liquid by increasing the pressure so that it can flow from one place to another or from a low surface to a high surface. In everyday life, the need for water is very useful, so it requires a pump to be able to take it or drain it. In this thesis research will be tested by making a pump prototype using a dynamo drive, and changing the shape of the impeller blade and the number of immersions to determine the resulting water pressure and the resulting water discharge. So that it can find out which impellers are effective in producing water and can drain water faster.